Peran Manajemen Loyalitas dalam Meningkatkan Pendapatan Ritel Modern: Indomaret - Anggit Dyah Kusumastuti; Chindy Martha Indhati; Ersa rahmawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The modern retail industry in Indonesia is experiencing increasing competition with the emergence of new players, including minimarkets, supermarkets, and e-commerce platforms. To maintain competitiveness and drive revenue growth, loyalty management strategies play a crucial role in customer retention and increasing transaction value. This study explores the role of loyalty management in boosting Indomaret's revenue through programs such as Indomaret Poinku, exclusive promotions, and digital payment integration. By implementing effective strategies, Indomaret successfully enhances customer retention, purchase frequency, and average transaction value. This study also compares Indomaret's loyalty strategy with competitors like Alfamart and identifies challenges in executing loyalty programs in modern retail. The findings indicate that a well-designed loyalty management strategy can significantly improve customer retention, strengthen consumer relationships, and positively impact business revenue growth.